A Deep Insight of Spermatogenesis and Hormone Levels of Aqua-Cultured Turbot (Scophthalmus maximus) - Liu, Yifan; Liu, Qinghua; Xu, Shihong; Wang, Yanfeng; Feng, Chengcheng; Zhao, Chunyan; Song, Zongcheng; Li, Jun (Frontiers in Marine Science, 2021)
Turbot (Scophthalmus maximus) is an important marine fish both in Europe and North China. Although there are plenty of studies on the reproduction of turbot, the complete cytological process of spermatogenesis remains unclear. In this study, we investigated the submicroscopic structure of total 23 types of male germ cells throughout the breeding season, with a relatively complete process of the primary spermatocytes. We found that the spermatid tail formed early at Spermatid Ⅱ, and there were at least 16 spherical mitochondria in the spermatozoa. The hepatosomatic index (HSI) and gonadosomatic index (GSI) both peaked during the breeding season. Preliminary analysis showed that the vitality of mature sperm was negatively correlated with the proportion of sperm deformity. The serum 3,5,3'-triiodothyronine (T3), 5-hydroxytryptamine (5-HT), testosterone (T), 17α,20β-Dihydroxy-4-pregnen-3-one (17α,20β-DHP), and 17β-estradiol (E2) all increased during the maturity period, with the change of T content most noticeable. Whereas in the testis, an overall high level of 11-ketotestosterone (11-KT) was more remarkable. The expression and localization of androgen receptor (AR) mRNA showed that the AR was highly expressed at the stages of Ⅱ (15 - 70g), with a slight rebound at the mature stages (Ⅳ(2200g) to Ⅴ(2500g)), whose change was ahead to the changes of T and 11-KT. Fluorescence in situ hybridization (FISH) analysis showed that the AR mainly distributed in but not limited to Sertoli cells. This study represents the most complete overview of the reproductive cycle and spermatogenesis of turbot, which provides an important reference for the reproduction research and the guidance of flatfish breeding.